건강보험심사평가원 자료를 이용한 대한민국 인공수정체 탈구의 발생률 및 위험인자 분석 - 강지혜(Ji Hae Kang); 염명인(Myeong In Yeom); 배윤종(Yoon jong Bae); 강동우(Dongwoo Kang); 박정민(Jung Min Park) (Daihan angwa haghoi jabji, 2024)
목적: 건강보험심사평가원 청구자료를 이용하여 2002-2020년까지의 대한민국 인공수정체 탈구의 발생률과 위험인자를 알아보고자하였다. 대상과 방법: 건강보험심사평가원에서 제공하는 건강보험 청구자료(Health Insurance Review & Assessment)를 이용하여 2002-2020년동안 인공수정체안 또는 인공수정체 1차 삽입술 코드를 처방받은 40세 이상 환자의 15%인 737,606명이 분석에 포함되었다. 2002-2020년의 인공수정체 탈구 매년 발생률과 위험인자 분석을 하였다. 결과: 2002-2020년 동안 인공수정체 탈구의 발생률은 0.20 ± 0.7%였다. 매년 발생률은 2002년 0.17%에서 2020년 0.34%로 통계학적으로 유의하게 증가하였다(p<0.001). 여자의 평균 매년 발생률은 0.1 ± 0.05%였으며 유의하게 증가하는 경향을 보이지 않았다(p>0.05). 남자의 평균 매년 발생률은 0.35 ± 0.13%였으며 유의하게 증가하는 경향을 보였다(p<0.001). 고도근시, 포도막염, 망막색소변성, 녹내장, 거짓비늘녹내장, 이전의 유리체망막수술력은 인공수정체 탈구의 유의한 위험인자였으며(p<0.001) 투석력, 고혈압은유의한 위험인자가 아니었다(p>0.05). 결론: 대한민국 인공수정체 탈구의 발생률은 0.2 ± 0.7%였으며 매년 증가하는 경향을 보이고 특히 남자군에서 증가하는 경향을 보이고 있었다. 고도근시, 포도막염, 망막색소변성, 녹내장, 거짓비늘녹내장, 이전의 유리체망막수술력은 인공수정체 탈구의 유의한 위험인자였다. Purpose: To analyze the incidence rate and risk factors of intraocular lens dislocation in South Korea from 2002 to 2020 using Health Insurance Review and Assessment Service data. Methods: This study included 15% of patients aged > 40 years had pseudophakia or intraocular lens primary implantation codes during 2002-2020 (737,606 patients). The annual incidence rate and risk factors of intraocular lens dislocation during 2002-2020 were analyzed. Results: The mean annual incidence rate of intraocular lens dislocation during 2002-2020 was 0.20 ± 0.7%. The annual incidence rate increased significantly from 0.17% in 2002 to 0.34% in 2020 (p < 0.001). The annual mean incidence rate for women was 0.1 ± 0.05%, and there was no increasing trend (p > 0.05). The annual mean incidence rate for men was 0.35 ± 0.13% and an increasing trend was found (p < 0.001). High myopia, uveitis, retinitis pigmentosa, glaucoma, pseudoexfoliative glaucoma and previous vitreoretinal surgery significantly increased the risk of intraocular lens dislocation (p < 0.001). Hemodialysis and hypertension were not significant risk factors (p > 0.05). Conclusions: The mean annual incidence rate of intraocular lens dislocation in South Korea was 0.2 ± 0.7%, and it showed an increasing trend, among men. High myopia, uveitis, retinitis pigmentosa, glaucoma, pseudoexfoliative glaucoma and previous vitreoretinal surgery significantly increased the risk of intraocular lens dislocation. KCI Citation Count: 0